2016
DOI: 10.18805/lr.v39i4.11260
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance of Campoletis chlorideae Uchida (Hymenoptera:Ichneumonidae), A larval parasitoid of Helicoverpa armigera(Hubner) hardwick in chickpea

Abstract: Climate change is likely to affect the insect host and the activity and abundance of biological control agents. Therefore, the present studies were conducted to understand the seasonal abundance of larval parasitoid, Campoletis chlorideae on chickpea at Pantnagar during the cropping season 2010-11 and 2011-12 revealed that the larval parasitoid exhibited its marked first appearance in 3 rd standard meteorological week (SMW) and attained peak population in 7 th (85.80%) and 8 th (87.65%) SMW, respectively. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…During 2019, no parasitoids were observed as the pest invaded the crop late in kharif season; during kharif 2020, the pest reappeared in June and its larval parasitoids were observed in the cropping season from 4 th week of October, 2020 to 1 st week of January, 2021. Degree of parasitization depends on the prevailing weather factors, and growth and development of the host (Pillai et al, 2016). The present study observed the native parasitoids' adaptability to parasitize FAW from Punjab.…”
Section: Resultsmentioning
confidence: 50%
“…During 2019, no parasitoids were observed as the pest invaded the crop late in kharif season; during kharif 2020, the pest reappeared in June and its larval parasitoids were observed in the cropping season from 4 th week of October, 2020 to 1 st week of January, 2021. Degree of parasitization depends on the prevailing weather factors, and growth and development of the host (Pillai et al, 2016). The present study observed the native parasitoids' adaptability to parasitize FAW from Punjab.…”
Section: Resultsmentioning
confidence: 50%
“…The temperature had a negative association with C. chlorideae larval and pupal periods and the parasitoid activity was found to cease at a temperature above 35C to 40C (Gupta and Raj, 2003;Teggelli et al, 2004;Dhillon and Sharma, 2008). Though Pillai et al (2016) as well as Divija and Agnihorti, (2021) reported that the maximum and minimum temperatures had a significant negative association with C. chlorideae incidence, which supports the present result, they have also pointed out that there exists a positive correlation between morning/evening RH and parasitoid incidence. As per Singh et al (2015) RH and rainfall did not play any precise function in C. chlorideae parasitization of H. armigera which is in agreement with the present findings.…”
Section: Natural Parasitization (%) Of H Armigera By C Chlorideaementioning
confidence: 99%
“…The minimum to a maximum threshold temperature and RH of 12C to 35C and 95%, respectively, were ideal for the survival, development and increased incidence of C. chlorideae (Kaur et al, 2000;Dhillon and Sharma, 2008). Pillai et al (2016) documented that the minimummaximum temperature as well as morning -evening RH in the range of 8.3C to 9.2C -23C to 24C and 89% to 90% -44% to 54%, respectively and nil rainfall were found to be favourable for the increased C. chlorideae incidence in Terai region of Uttarakhand. .…”
Section: Natural Parasitization (%) Of H Armigera By C Chlorideaementioning
confidence: 99%
“…Changes in distribution patterns can lead to the diversity of organisms. In essence, climatic factors can directly affect species composition, breeding habitat, survival, and population of Hymenoptera insects (Pillai et al 2016;Masika et al 2017;Maulina et al 2018).…”
Section: Correlation Of Parasitic Hymenoptera With Their Microclimatesmentioning
confidence: 99%